Non-destructive testing of weld specimen using phased array ultrasonic procedures - Chong, Marcos Zhen You (2018)
Structural integrity is the upmost importance in all engineering sectors to ensure safety of all its users. To facilitate structural integrity assessment, one of the most commonly used techniques are non-destructive testing (NDT). These techniques do not alter the inspected components and come in different techniques to fit the operator’s needs. These techniques comprise ultrasonic testing, liquid penetrant, magnetic-particle, radiography and eddy-current. There are different types of ultrasonic testing, with the conventional ones such as A-scan, B-scan and C-scan and the newer ones such as phased array and time of flight diffraction (TOFD). This paper focuses on ultrasonic testing on metallic specimens, in particular phased array technology. The author had compare results of phased array and conventional A-scan using an educational kit of weld specimens to evaluate their accuracy in depth location and length location. In addition, studies on phased array ability to replicate defects had been explored using 2 fabricated specimens with measurable side views and comparison had been made across conventional A-scan. In general, phased array technology has evidently more advantages and can provide results of higher accuracy over conventional A-scan for most inspection. The phased array data provided clear visualisation to better determine the location of defects over conventional A-scan, hence significantly reduces operator error. It also allows operators to display multiple data from a single scan, allowing necessary results to be sieve more quickly and easily. On top of that, the multiple elements within the array probe allows wider scan area, thus reducing the inspection time of phased array as compared to conventional A-scan. Therefore, phased array is considered better than conventional A-scan. Reflected waves off its initial source were found to be the main factor limiting phased array from replicating defects. As beams did not hit the defects perpendicularly, waves were reflected away and often not received by the probe. Hence, missing pieces of information limits phased array technology from replicating the defect accurately. However, the author believes it is co-related to the active elements within the probe and more studies are required to be carried. Even though this technology may have proved to be more superior in obtaining the rough outline of certain defects, it is still not capable of obtaining the perfect shape of the defect.